11. KEPEMIMPINAN TRANSFORMASIONAL DAN DAMPAK TERHADAP KINERJA KARYAWAN PADA IKM BERBASIS EKSPOR - Widiartanto, Widiartanto (FORUM, 2014)
The study is aimed at examining the effect of transformational leadership on employee performance through employee empowerment and organizational commitment as a mediating variables of the cluster of carving copper in Cepogo Boyolali. The research samples cover 30 employees of the CV. Intermedia Logam as part of a cluster of carving copper. Sample determination applies totals sampling or population sampling in which all members of the population are used as research samples. In examining the established model relationship, the data are analyzed by using path analysis. The results reveal: transformational leadership gives positive and significant effect on employee empowerment; transformational leadership gives positive and significant effect on employee performance; employee empowerment gives positive and significant effect on employee performance; organizational commitment as a mediating variables between transformational leadership and employee performance, employee empowerment as a mediating variables between transformational leadership and employee performance, and organizational commitment as a mediating variables between employee empowerment and employee performance. This research suggests that companies disseminate the vision, mission and goals; conduct of training; and providing incentives to the agreement in order to achieve employment targets.